Peran Keluarga Dalam Mencegah Kenakalan Remaja (Studi Kasus Lingkungan Keluarga Saombo Koto Gunungsitoli) - Gulo, Vinal Fornia; Harefa, Wenti Kristiani (Media Hukum Indonesia (MHI), 2025)
Juvenile delinquency is one of the social problems that impacts the development of the younger generation, especially in the Saombo Village, Gunungsitoli City. This study aims to examine the role of the family in preventing juvenile delinquency in the area. The method used is a qualitative approach with data collection techniques through observation, interviews, and documentation of several families and local community leaders. The results of the study indicate that the family has a central role in the formation of adolescent character, through consistent parenting, open communication, and active supervision. Families who apply democratic parenting tend to be more successful in preventing their children from falling into deviant behavior. Conversely, lack of attention and emotional closeness from parents is one of the triggers for delinquency. Thus, efforts to prevent juvenile delinquency in Saombo Village need to start from strengthening the function of the family as the first and main educational environment for children.